EFFORT OF STEEL PIPE JACKING IN TERMS OF IMPERFECTION PIPES AND HETEROGENEITY OF GROUND - Górski, K.; Ignatowicz, R. L. (Science and Transport Progress, 2016)
Purpose. The article presents problem of the influence of local inhomogeneities of ground on the internal forces in the steel pipe. Methodology. The authors presented the differences in the distributions of earth pressures for the pipes. One of the most common methods is the microtunneling technology. The examples of numerical analysis by finite element method (FEM) have been calculated. Findings. The results of numerical analysis are presented for selected ground conditions and the distribution of internal forces in the flexible section of the steel pipe is also shown. Originality and Practical value. The obtained results clearly show the influence of flexural rigidity of the pipe on the internal forces, the influence of flexural rigidity and the soil stiffness on the size of the bending moments in the steel of pipe jacking. They depend on the interaction of soil – steel pipe.